Trade, aid and security : an agenda for peace and development - Brown, Oli...[et al.] (Earthscan LondonGB, 2007)
Focuses on aspects such as - ensuring trade and aid policies are conflict-sensitive, fostering responsible business conduct, reducing the trade in 'conflict resources', promoting good governance and helping countries to manage more effectively the revenues they receive from natural resources and aid.